Virginity as a Symbol of Honor: A Gendered Analysis of Kandangan Village through the Lens of Simone de Beauvoir - Ni’mah, Durriyatun; Sakti Ritonga (Journal of Islamic Philosophy and Contemporary Thought, 2023)
The concept of virginity is often viewed as a valuable asset before marriage, which is highlighted in social discourse involving religion, culture, and morality. In patriarchal societies, female virginity is often considered a symbol of self-worth, while male virginity receives less attention. Women who engage in sexual intercourse for the first time often face social judgment and stigma, while their rights to understand and interpret their bodies are often ignored. This phenomenon reflects restrictions on women’s roles and rights within the social structure. This study aims to analyze how the value of virginity is perceived in traditional society, specifically in Kandangan Village, Trucuk Subdistrict, Bojonegoro District. Using Simone de Beauvoir's existentialist feminism theory as a theoretical framework, this research employs a descriptive-qualitative research method with data analysis from interviews, books, field notes, photos, and videos. The findings reveal that societal views on virginity play a significant role in reinforcing gender inequality, with women often facing social judgment and exclusion. Despite differing perspectives between religious leaders and the general public, the concept of virginity remains a symbol of injustice that disadvantages women.